Weight Implications on Pregnancy Outcomes - Carter, Lindsay Elizabeth (MacEwan University Student eJournal, 2016)
The incidence of rising weight in reproducing women has potential for adverse maternal and fetal outcomes, both short and long term. The purpose of the project was to identify the extent of potential implications resulting from maintaining a body mass index larger than 25 throughout a pregnancy. Select authors have conducted quantitative, retrospective cohort studies by requesting participants to complete a questionnaire during pregnancy providing information on variables of social determinants of health with a control study of woman with a BMI under 25 and excluding mothers without a recorded BMI in antenatal records and mothers with pre-existing diabetes. Research resulted in overarching implications for both maternal and fetal well-being with added potential burden on the health care system. Neonate’s born under influence of a maternal BMI larger than 25 risk complications including preterm birth, congenital anomalies, fetal macrosomia, and death. Mothers are at increased risk for preeclampsia, gestational diabetes, postpartum hemorrhage, caesarian section and require more healthcare services. Continued longitudinal studies may provide greater insight into the life course trajectories of children born under such circumstances, and offer interventions appropriate to aid consequences of weight implications on pregnancy outcomes. Furthermore, additional studies on appropriate and safe interventions throughout the pregnancy may minimize potential risks on maternal and fetal well-being. This discussion is designed to explain the gravity of weight juxtaposed with pregnancy, and provide strategies aimed at optimizing health outcomes.